Early life travelling does not increase risk of atopic outcomes until 15 years: results from GINIplus and LISAplus. Issue 3 (13th February 2017) - Markevych, I.; Baumbach, C.; Standl, M.; Koletzko, S.; Lehmann, I.; Bauer, C.‐P.; Hoffmann, B.; von Berg, A.; Berdel, D.; Heinrich, J.
Summary: Background: Westernized lifestyle has been blamed for allergy epidemics. One of its characteristics is increased distances and frequency of travelling from early life onwards. Early life travelling to places which substantially differ from home environment in terms of climate, vegetation and food could increase the exposure to further unknown allergens and hence promote the development of allergies, but no epidemiological study has investigated this speculation. Methods: Detailed data on travelling during the first 2 years of life as well as a range of atopic outcomes along with potential confounders up to age 15 years were collected prospectively within two large population‐based multicentre German birth cohorts – GINIplus and LISAplus. Farthest travelling destination (within Germany; middle/northern/eastern Europe; southern Europe; outside Europe), total number of trips and their combination were considered as exposures. Six atopic outcomes were used: (1) doctor‐diagnosed asthma, (2) doctor‐diagnosed allergic rhinitis, (3) nose and eye symptoms, (4) sensitization to food allergens, (5) sensitization to indoor and (6) outdoor inhalant allergens. Longitudinal associations between each exposure and health outcome pair were analysed using generalized estimation equations (GEEs). Results: The results of our longitudinal analyses of 5674 subjects do not support the research hypothesis that travelling abroad to different regions in Europe or beyond Europe and frequency of travelling increase prevalence of doctor‐diagnosed asthma and allergic rhinitis, nose and eye symptoms and allergic sensitization up to 15 years of age. Furthermore, there was no indication of age‐varying effects. Conclusions: Early life travelling does not seem to increase risk of atopic outcomes. Nevertheless, as we could not account for the type of visited environment or length of stay, these first findings should be interpreted with caution.